Automatic and Strategic Measures as Predictors of Mirror Gazing Among Individuals with Body Dysmorphic Disorder Symptoms - Clerkin, Elise M. (2009)
The current study tests cognitive-behavioral models of body dysmorphic disorder (BDD) by examining the relationship between cognitive biases and correlates of mirror gazing. To provide a more comprehensive picture, we investigated both relatively strategic (i.e., available for conscious introspection) and automatic (i.e., outside conscious control) measures of cognitive biases in a sample with either high (n=32) or low (n=31) BDD symptoms. Specifically, we examined the extent that 1) explicit interpretations tied to appearance, as well as 2) automatic associations and 3) strategic evaluations of the importance of attractiveness predict anxiety and avoidance associated with mirror gazing. Results indicated that interpretations tied to appearance uniquely predicted self-reported desire to avoid, while strategic evaluations of appearance uniquely predicted peak anxiety associated with mirror gazing, and automatic appearance associations uniquely predicted behavioral avoidance. These results offer considerable support for cognitive models of BDD, and suggest a dissociation between automatic and strategic measures.